1993
DOI: 10.1085/jgp.101.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Divalent cation competition with [3H]saxitoxin binding to tetrodotoxin-resistant and -sensitive sodium channels. A two-site structural model of ion/toxin interaction.

Abstract: Monovalent and divalent cations competitively displace tetrodotoxin and saxitoxin (STX) from their binding sites on nerve and skeletal muscle Na channels. Recent studies of cloned cardiac (toxin-resistant) and brain (toxinsensitive) Na channels suggest important structural differences in their toxin and divalent cation binding sites. We used a partially purified preparation of sheep cardiac Na channels to compare monovalent and divalent cation competition and pH dependence of binding of [3H]STX between these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 64 publications
5
34
0
Order By: Relevance
“…4 However, it is known that TTX affinity depends on [Na] o . 22,23 Our K D is similar to previous reports using low [Na] o in cardiac ventricular myocytes 5,13 and after correction for the effect of [Na] o 22 is in agreement with the micromolar range reported previously. The dose-response curve at Ϫ10 mV is well fitted with a double Hill curve (gray line, Figure 1B): if it is assumed that the K D of TTX-resistant current is 628 nmol/L (and the Hill coefficients of both TTX-resistant and TTX-sensitive currents are 1), this gives a K D for the TTX-sensitive current of 8.8 nmol/L (ESE, 6.4; CI, 27) and the fraction of TTX-resistant and TTX-sensitive currents as 0.86 and 0.14 (ESE, 0.03; CI, 0.11), respectively.…”
Section: Presence Of Ttx-resistant and Ttx-sensitive I Na In Rat Ventsupporting
confidence: 91%
See 3 more Smart Citations
“…4 However, it is known that TTX affinity depends on [Na] o . 22,23 Our K D is similar to previous reports using low [Na] o in cardiac ventricular myocytes 5,13 and after correction for the effect of [Na] o 22 is in agreement with the micromolar range reported previously. The dose-response curve at Ϫ10 mV is well fitted with a double Hill curve (gray line, Figure 1B): if it is assumed that the K D of TTX-resistant current is 628 nmol/L (and the Hill coefficients of both TTX-resistant and TTX-sensitive currents are 1), this gives a K D for the TTX-sensitive current of 8.8 nmol/L (ESE, 6.4; CI, 27) and the fraction of TTX-resistant and TTX-sensitive currents as 0.86 and 0.14 (ESE, 0.03; CI, 0.11), respectively.…”
Section: Presence Of Ttx-resistant and Ttx-sensitive I Na In Rat Ventsupporting
confidence: 91%
“…The K D of the TTX-sensitive current is consistent with published data (1 to 25 nmol/L), 4 even after correction for the effect of [Na] o (which has a similar effect on cardiac and neuronal Na channels). 22 The fraction of TTX-sensitive I Na (14Ϯ3%) is in the range of other cardiac preparations (5% to 30%). 5,6,10,13 …”
Section: Presence Of Ttx-resistant and Ttx-sensitive I Na In Rat Ventmentioning
confidence: 97%
See 2 more Smart Citations
“…One of these (trimethyloxonium ion) revealed that acidic amino acids were important in the binding of TTX and STX. Pretreatment with this reagent abolished the channel's ability to bind the toxin, whereas pre-exposure of the channel to the toxin protected it from protein modification (Barchi and Weigele 1979;Doyle et al 1993;Spalding 1980;Worley et al 1986). Later, after Na channel genes were sequenced and successfully expressed in recombinant systems, mutagenesis studies pinpointed a series of carboxylate sidechain-containing amino acids in homologous positions within each of the four domains of the channel involved in binding the toxin (Terlau et al 1991) and were hypothesized to form two predominantly negatively charged rings near the ion pore.…”
Section: Effects Of Na Channel Modificationmentioning
confidence: 99%